PRICING DAX INDEX WARRANTS WITH THE BLACK-SCHOLES MODEL - Nurmi, Markus (My University, 2019)
This thesis investigates covered warrants market in Finland and examines the suitability of the Black-Scholes option pricing model for the pricing of covered warrants. The purpose of this study is to test and evaluate the predictive power of different volatility estimates for pricing DAX index warrants when the Black-Scholes model is applied. Different volatility estimates are derived from the market premiums of index warrants quoted on Nasdaq Helsinki, calculated from the DAX index closing levels and picked up from the VDAX volatility index data. Market premiums of warrants are compared against theoretical warrant prices generated by using the Black-Scholes option pricing model. The empirical results can be summarized as follows: 1.) The Black-Scholes model does not value all warrants accurately. 2.) Implied volatility outperforms other volatility estimates. 3.) Call warrants are underpriced relative to puts. 4.) The implied volatilities of call and put warrants are not equal, indicating potential inefficiency in the warrant markets.
Keywords: Black-Scholes model; covered warrant; implied volatility; put-call parity; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|